Antidiabetic Action of Alfalfa (Medicago sativa) Leaves Powder on Type II Diabetic Patients - Burhan A. Salih; Kokaz O. Azeez (Polytechnic Journal)
Type II diabetes is a common metabolic disorder that is specified by hyperglycemia resulting from defects in insulin action. Alfalfa (Medicago sativa) is a medicinal plant (leaves, flower, and seeds) used traditionally as antidiabetic. This study is designed to investigate the short-term antidiabetic action of alfalfa leaves powder in patients with Type II diabetes mellitus. 12 volunteers suffering from type II diabetes were undertaken besides 12 healthy individuals. The subjects were divided into four groups including healthy control, diabetic control, which received an only meal, and the third and fourth groups were healthy and diabetic subjects which received alfalfa leaves powder within the meal. A standard test meal was supplemented with 8 g of alfalfa. The results showed that alfalfa leaves significantly (P = 0.03) reduces blood sugar 2 h after meal from 344.4 mg/dl to 300.75 mg/dl in the diabetic subject, in addition to the elevation of serum insulin levels (P = 0.02) at 30 min and elevation further increased (P = 0.06) at 120 min. This finding suggested that alfalfa leaves could be applied as a therapy against Type II diabetes.